Prevalence of hepatitis B virus infection and its associated factors among pregnant women in Ethiopia: a systematic review and meta-analysis of data published from 2003 to 2024 - Sintayehu Tsegaye Bitew; Yeshiwas Genanaw Mekonnen; Habtamu Belay Hailu (Archives of Public Health)
Abstract Background Numerous epidemiological studies on hepatitis B virus among pregnant women in Ethiopia have been conducted, showing significant variation over time and between different geographical regions. The aim of this systematic review and Meta-analysis is to estimate the overall prevalence of hepatitis B virus infection and its associated factors among pregnant women in Ethiopia. Methods We use the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for articles. All observational published studies were retrieved using relevant search terms PubMed, Embase, web of science and google scholar databases. Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instruments for observational studies was used for critical appraisal of the included articles. The meta-analysis was done with STATA version 18 software. The I2 statistics were used to test heterogeneity whereas Begg’s and Egger’s tests were used to assess publication bias. The pooled prevalence was presented using the forest plot. Results Forty –three studies with a total of 17,056 participants were included in this systematic review and meta-analysis. The pooled prevalence of the HBV infection among pregnant women was 6%(95% CI: 5.0, 7.0). a high pooled prevalence HBV infection among pregnant women was found in Tigray 7%(95% CI: 4.0, 8.0) and Somali region 7%(95% CI: 4.0, 11.0). history of surgical procedure, having multiple sexual partners, history of body tattooing, history of abortion, history of sharing sharp material, blood transfusion and family history of HBV were significant risk factors associated with HBV among pregnant women in Ethiopia. Conclusion In conclusion, this systematic review and meta-analysis provided evidence regarding the intermediate prevalence of HBV among pregnant women in Ethiopia and also showed history of surgical procedures, multiple sexual partners, body tattooing, sharing sharp objects, abortion, blood transfusions, and family history of HBV infection were associated factors. The findings highlight the need of health education to prevent the spread of HBV infection among pregnant women.